Patient and provider perspectives on how trust influences maternal vaccine acceptance among pregnant women in Kenya - Stacy W. Nganga; Nancy A. Otieno; Maxwell Adero; Dominic Ouma; Sandra S. Chaves; Jennifer R. Verani; Marc-Alain Widdowson; Andrew Wilson; Irina Bergenfeld; Courtni Andrews; Vincent L. Fenimore; Ines Gonzalez-Casanova; et al. (BMC, 2019)
Abstract Background Pregnant women and newborns are at high risk for infectious diseases. Altered immunity status during pregnancy and challenges fully vaccinating newborns contribute to this medical reality. Maternal immunization is a strategy to protect pregnant women and their newborns. This study aimed to find out how patient-provider relationships affect maternal vaccine uptake, particularly in the context of a lower middle- income country where limited research in this area exists. Methods We conducted semi-structured, in-depth narrative interviews of both providers and pregnant women from four sites in Kenya: Siaya, Nairobi, Mombasa, and Marsabit. Interviews were conducted in either English or one of the local regional languages. Results We found that patient trust in health care providers (HCPs) is integral to vaccine acceptance among pregnant women in Kenya. The HCP-patient relationship is a fiduciary one, whereby the patients' trusts is primarily rooted in the provider's social position as a person who is highly educated in matters of health. Furthermore, patient health education and provider attitudes are crucial for reinstating and fostering that trust, especially in cases where trust was impeded by rumors, community myths and misperceptions, and religious and cultural factors. Conclusion Patient trust in providers is a strong facilitator contributing to vaccine acceptance among pregnant women in Kenya. To maintain and increase immunization trust, providers have a critical role in cultivating a positive environment that allows for favorable interactions and patient health education. This includes educating providers on maternal immunizations and enhancing knowledge of effective risk communication tactics in clinical encounters.